A Review of Indonesian Business Start-Up Incubator Models - Annas, Mohammad; Meilinda, Vivi (Pandawan Sejahtera Indonesia, 2023)
The new global economy has a need for business incubation, which is brought on by deregulation, globalization, and the quick and significant advances in the fields of technology, telecommunications, and digitization. Every business incubator must be skilled at developing startup company strategy and have links to financial resources, related business communities, and business information and consultancy. Because the Business Incubator may strengthen the capacity and business performance of new science and technology-based entrepreneurial prospects, its role in the development of Innovative SMEs is particularly strategic.